2018
DOI: 10.1021/acs.jpca.7b11952
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Bonding Acceptor Character of Be3, the Beryllium Three-Membered Ring

Abstract: The ability of Be as a hydrogen bond acceptor has been explored by studying the potential complexes between this molecule and a set of hydrogen bond donors (HF, HCl, HNC, HCN, HO, and HCCH). The electronic structure calculations for these complexes were carried out at the MP2 and CCSD(T) computational levels together with an extensive NBO, ELF, AIM, and electrostatic potential characterization of the isolated Be system. In all the complexes, the Be-Be σ bond acts as electron donor, with binding energies betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 47 publications
(63 reference statements)
1
30
0
Order By: Relevance
“…It is worth to mention that the binding energies for simple cyclopropane complexes calculated at the MP2/aug’‐cc‐pVTZ level were presented recently to compare them with the analogues complexes of the cyclic Be 3 moiety . Few cyclopropane complexes analyzed here were presented also in the above‐mentioned study .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…It is worth to mention that the binding energies for simple cyclopropane complexes calculated at the MP2/aug’‐cc‐pVTZ level were presented recently to compare them with the analogues complexes of the cyclic Be 3 moiety . Few cyclopropane complexes analyzed here were presented also in the above‐mentioned study .…”
Section: Resultsmentioning
confidence: 97%
“…It was found that the A−H…σ interactions are not meaningless here, however the absolute value of the binding energy (−E bin ) does not exceed 5 kcal mol −1 , the strongest interaction was detected for the Be 3 …HF complex . In the latter study the binding energies of the Be 3 complexes are compared with the corresponding complexes with the C 3 H 6 species playing a role of the Lewis base . The cyclopropane complexes are characterized by slightly stronger interactions than their Be 3 counterparts …”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, albeit this analysis of MESP topology is breaking through in current research, its application to large systems is being hindered by the cost of computing accurate values of MESP and its derivatives. Thus, the introduction of more efficient procedures like that proposed herein has greatly facilitated this type of studies, and several works using the new algorithms have appeared in recent literature [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%